INDONESIAN NATION BUILDING DISCOURSES IN JAPANESE NEWSFILMS, 1942–1945 - Tyas, Agnes Siwi Purwaning (Moestopo International Review on Social, Humanities, and Sciences, 2024)
As an important chapter in Indonesia's modern history, Japanese occupation had profound impacts on every aspect of the nation's culture and society. It was at this time that Japan started to develop and manage Indonesian film industry which was crucial in providing the idealized and positive role models needed to strengthen and reaffirm Indonesian nationalism. Considering the importance of this industry, this paper aims to investigate how the concepts of nationalism and national characters unique to Indonesia are defined and reinforced in wartime newsreels used as social communication tools under Japanese imperial control. The method used in this study is discourse analysis to observe the ideological messages inside the newsreels important for nation building. The result of this study shows that the main elements in films of this period are systemically designed to construct narrative in line with Indonesia’s nation building despite its nature as media of Japanese propaganda. Through the use of cinematic discourses, newsreels tend to visualize images of an emerging nation having successfully developed a sense of identity and national belonging. This analysis is further contextualized with the propaganda reports of the time to identify how the Japanese inspired nationalism is still embodied in modern texts.